The safety of vedolizumab for ulcerative colitis and Crohn's disease. Issue 5 (18th February 2016) - Colombel, Jean-Frédéric; Sands, Bruce E; Rutgeerts, Paul; Sandborn, William; Danese, Silvio; D'Haens, Geert; Panaccione, Remo; Loftus, Edward V; Sankoh, Serap; Fox, Irving; Parikh, Asit; Milch, Catherine; et al.
Abstract : Objective: Vedolizumab is a gut-selective antibody to α4 β7 integrin for the treatment of ulcerative colitis (UC) and Crohn's disease (CD). We report an integrated summary of the safety of vedolizumab. Design: Safety data (May 2009–June 2013) from six trials of vedolizumab were integrated. Adverse events were evaluated in patients who received ≥1 dose of vedolizumab or placebo and were reported as exposure-adjusted incidence rates as the number of patients experiencing the event per 100 person-years (PYs) of exposure. Predictors of serious infection were assessed using a Cox proportional hazards model. Results: In total, 2830 patients had 4811 PYs of vedolizumab exposure (median exposure range, 1–1977 days). No increased risk of any infection or serious infection was associated with vedolizumab exposure. Serious clostridial infections, sepsis and tuberculosis were reported infrequently (≤0.6% of patients). No cases of progressive multifocal leucoencephalopathy were observed. Independent risk factors for serious infection in UC were prior failure of a tumour necrosis factor α antagonist (HR, 1.99; 95% CIs 1.16 to 3.42; p=0.0122) and narcotic analgesic use (HR, 2.68; 95% CI 1.57 to 4.58; p=0.0003), and in CD were younger age (HR, 0.97; 95% CI 0.95 to 0.98; p<0.0001), corticosteroid (HR, 1.88; 95% CI 1.35 to 2.63; p=0.0002) or narcotic analgesic use (HR, 2.72; 95% CI 1.90 to 3.89; p<0.0001). Investigator-defined infusion-related reactions were reported for ≤5% of patients in each study. Eighteen vedolizumab-exposed patients (<1%) were diagnosed with a malignancy. Conclusions: Vedolizumab has a favourable safety profile with low incidence rates of serious infections, infusion-related reactions and malignancies over an extended treatment period. Trial registration number: NCT01177228, NCT00619489, NCT00783718, NCT00783692, NCT01224171, NCT00790933 .